THE ATTRIBUTES OF GOVERNMENT EFFECTIVENESS: AN ISLAMIC ECONOMIC THOUGHT - Lakhi Muhammad; Gul-e- Rana (Share: Jurnal Ekonomi dan Keuangan Islam, 2018)
The index of government effectiveness captures perceptions of the quality of public services, the quality of the civil service and the degree of its independence from political pressures, the quality of policy formulation and implementation, and the credibility of the government's commitment to such policies. These perceptions are the main attributes of Government Effectiveness Index. The majority of the OIC member states remained negative on Government Effectiveness Index till 2014. What are the Islamic thoughts on these attributes of Government Effectiveness Index? How the government effectiveness can be improved according to the Islamic economic thoughts? These questions are dealt with in this exploratory paper. In the Muslim world, most of the countries are with low income and tax collection is less. This less collection creates a budget pressure to co-brand with government expenditures. The religion Islam not only confesses to the state to take of the poor but to the wealthy people also have a responsibility to take care of the poor. This Islamic thought will support the government to mark some strategies to motivate the wealthy for participating in poverty reduction programs.===============================================Atribut Efektivitas Pemerintah: Suatu Pemikiran Ekonomi Islam - Indeks efektivitas pemerintah menangkap persepsi kualitas layanan publik, kualitas layanan sipil dan tingkat independensinya dari tekanan politik, kualitas formulasi kebijakan dan implementasi, dan kredibilitas komitmen pemerintah terhadap kebijakan tersebut. Persepsi ini merupakan atribut utama dari Indeks Efektivitas Pemerintah. Mayoritas negara anggota OKI tetap negatif pada Indeks Efektivitas Pemerintah hingga 2014. Apa pemikiran Islam tentang atribut-atribut Indeks Efektivitas Pemerintahan ini? Bagaimana efektivitas pemerintah dapat ditingkatkan sesuai dengan pemikiran ekonomi Islam? Pertanyaan-pertanyaan ini dibahas dalam makalah eksplorasi ini. Dalam dunia Islam, rata-rata negara mempunyai pendapat dan pungutan pajak yang rendah. Hal ini mengakibatkan tekanan anggaran yang tidak bisa mengimbangi pengeluaran pemerintah. Agama Islam tidak hanya mewajibkan negara untuk mengurus orang, tetapi juga dibebankan kepada orang-orang kaya. Pemikiran seperti ini akan mendukung pemerintah untuk menciptakan strategi agar orang-orang kaya termotivasi untuk berpartisipasi dalam program pengentasan kemiskinan.